Potential of Guava (Psidium guajava L.) as an Additional Therapy for Dengue Fever - Mahalaksmi, Alika Sabrina; Salam, Anisa Rakhmania; Rania, Athaya Putri; Ekapratista, Belinda Nabilah; Wardhana, Brahma Wisnu Kusuma; Novian, Farah Kusuma Wardhani; Laksmi, Farika Dyani Laksmi; Najlaa, Fatimah Ahla; Pradnyanantha, I Putu Bagus; Hardiyanti, Merry; Haliza, Nabila Nur; Pramesti, Ragil Putri; Amalia, Savira Rizky Meisya; Kusumawati, Idha; Widyowati, Retno (Universitas Airlangga, 2024)
Dengue fever had been a global health problem for over five decades, especially in tropical and subtropical countries. It was caused by a viral infection that spread from mosquito to human. Natural sources had the potential to serve as an alternative therapy for dengue fever, such as Psidium guajava L. Its leaves contained several compounds and exhibited various bioactivities. This research aimed to explore the potential of Psidium guajava as an additional therapy for dengue fever patients. The method used was a narrative literature review that searched literature in primary data sources such as national and international journals through databases like PubMed and Scopus. The results reported that quercetin was one of the compounds found in Psidium guajava that affected dengue fever. It suppressed the intracellular replication of dengue virus type 2 (DENV-2) and inhibited ATPase in DENV-4. Additionally, quercetin also stimulated stem cell factors in bone marrow stromal cells to produce thrombopoietin, which functioned to regulate platelet production in the spinal cord. Thus, Psidium guajava had the potential and effectiveness to be used as an alternative therapy for dengue fever.Keywords: Dengue Fever, Guava, Quercetin, Thrombopoietin, Alternative Therapy